The Extent of Principals' Practice of Creative Management in Mafraq Governorate - Lafi Makhareez; Enas Al- Bado; Sari Malahim; Mousa Atieh (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to reveal the extent of principals' practice of creative management in Mafraq Governorate. To achieve the objectives of the study, the researchers used the descriptive approach. The sample of the study consisted of 100 principals from public schools affiliated to the Directorate of Education of Mafraq governorate during the academic year 2016-2017. A questionnaire that consisted of (18) items was developed. The items focused on the degree of principals' practice of creative management. The validity and reliability of the questionnaire were verified. The level of practice of principals for creative management in the schools of directorates of the province of Mafraq ranged from low to medium. In addition, there are no statistically significant differences at the significance level (α = 0.05) in all areas of the study instrument due to the effect of gender and years of experience variables. This study recommends training school principals on how to employ creative work methods in administrative work; in order to develop their managerial performance. In addition, involving school principals and members of the local community in making appropriate decisions that are consistent with the needs and conditions of the school, and giving them more powers commensurate with the size of the tasks assigned to them.